Charismatic Leadership of Kiai in Developing an Organizational Culture of Islamic Boarding School - Hariyadi, Ahmad; Rustono, Rustono; Eko Pramono, Suwito; Yanto, Heri (Universitas Negeri Semarang, 2018)
This research was designed as a case study conducted by collecting data from Islamic Boarding School (Pesantren) Raudlatut Tholibin Leteh and Al-Anwar Sarang. Based on the data from both sites, the analysis was conducted to understand the differences and similarities of both cases as the basis for determining the characteristics of cultural development and typology, the role, the characteristics of kiai's charismatic leadership in building the pesantren organization culture. The result of the study shows that the organizational culture developed at Pesantren Raudlatut Tholibin Leteh includes (1) daily activities, such as praying in congregation, studying the Qur'an, following the pesantren-madrasah, regular and sorogan recitation, and learning; (2) weekly activities include speech training, sorogan Fiqh, Alfiyah study, Fiqh deliberation, tahlil, maulid or manaqib reading, sorogan nahwu, gymnastics, and English lessons; (3) annual activities, among other things, include the Muharram, Ramadan, Eid al-Fitr, Eid al-Adha celebrations. The organizational culture developed in Pesantren Al-Anwar includes (1) daily activities of the male learners covering the Qur'an tadarus in each khos, Qur'an recitation, MGS & MHD school, mudzakaroh mahally, MGS afternoon consultation, study group, Ma'had Aly learning, MHD deliberation, Fathul Qorib deliberation, and Fathul Mu'in deliberation. The daily activities of female learners include Wirdil Lathif, Rothib Al Athos, and sholawat Masyisyiyah reading, as well as Qur'an recitation, fan Nahwu recitation, MPG deliberation, muhadloroh deliberation, Takhoshush learners recitation, teaching by KH. Maimoen Zubair, teaching by KH. Majid Kamil, fan fiqh study, 41 times Yasin reading, level discussion, and Fathul Qorib deliberation; (2) the weekly activities for male learners include muhafadhah, dziba'iyyah & khitobiyyah, and sorogan; female learners’ activities include recitation of Yasin fadhilah and Asmaul Husna, as well as Yasin and Burdah recitation, Dibaiyyah, tabligh (training of da'wah), Burdah training, math and English courses, muhafadhoh kubro, muhafadhoh tawajjuh (memorizing), Ta'limul Muta 'allim, and muroja'ah learning; (3) the annual activities include Muharram, Maulud, Ramadan, Idul Fitri, and Eid al-Adha celebrations.